Neuro-computational account of how mood fluctuations arise and affect decision making - Fabien Vinckier (Nature Portfolio, 2018)
Fluctuations in mood are known to affect our decisions. Here the authors propose and validate a model of how mood fluctuations arise through a slow integration of positive and negative feedback and report the resulting key changes in brain activity that modulate our decision making.